Clinical features and outcomes of patients with wheat-dependent exercise-induced anaphylaxis: a retrospective study - Zhirong Du; Xiang Gao; Junda Li; Lun Li; Juan Liu; Jia Yin (Allergy, Asthma & Clinical Immunology, 2022)
Abstract Background Wheat-dependent exercise-induced anaphylaxis (WDEIA) is a serious and potentially life-threatening form of wheat allergy. Further episodes can only be prevented by avoiding wheat ingestion or avoiding exercise after wheat intake. Anaphylaxis may recur in some patients post-diagnosis. This study aimed to analyze the clinical features and management/outcomes of WDEIA in China. Methods We retrospectively analyzed the clinical characteristics, and laboratory testing of 197 patients with WDEIA. After diagnosis, the patients were followed up as outpatients to evaluate dietary/exercise choice and clinical outcomes. Results Among the 197 WDEIA patients (median age, 37 years), 53.8% were male and 28.4% had other allergic disorders. The median duration of anaphylaxis before diagnosis was 16 months. Significant delays in diagnosis (> 1 years) were recorded in 52.7% of the patients, which has not decreased by years (P = 0.064). Exercise (83.8%), alcohol (12.2%), and nonsteroidal anti-inflammatory drugs (7.1%) were the most common cofactors. The most common clinical features were urticaria (100%), loss of consciousness (82.7%), dyspnea (50.8%), and hypotension (47.2%). Of the 197 eligible patients, 155 responded (78.7%), and 124 (80.0%) of which had no anaphylaxis post-diagnosis. A wheat-free diet prevented future anaphylaxis in 91.7% of the patients, followed by the avoidance of wheat combined with exercise (87%) and reduced wheat intake combined with exercise avoidance (80.5%). Conclusion The diagnosis of WDEIA is frequently delayed. Therefore, when patients present with unexplained anaphylaxis, the possibility of WDEIA should be considered. A wheat-free diet or avoiding wheat combined with exercise or reduced wheat combined with exercise avoidance helps to significantly reduce the onset of future anaphylaxis. However, approximately one-fifth of patients continue to experience anaphylaxis post-diagnosis. Thus, these patients must always carry epinephrine autoinjectors.